Recommendations for Management of Patients with Carotid Stenosis - Arijana Lovrencic-Huzjan; Tatjana Rundek; Michael Katsnelson (Stroke Research and Treatment)
Stroke is a one of the leading causes of morbidity and mortality in the world. Carotid atherosclerosis is recognized as an important factor in stroke pathophysiology and represents a key target in stroke prevention; multiple treatment modalities have been developed to battle this disease. Multiple randomized trials have shown the efficacy of carotid endarterectomy in secondary stroke prevention. Carotid stenting, a newer treatment option, presents a less invasive alternative to the surgical intervention on carotid arteries. Advances in medical therapy have also enabled further risk reduction in the overall incidence of stroke. Despite numerous trials and decades of clinical research, the optimal management of symptomatic and asymptomatic carotid disease remains controversial. We will attempt to highlight some of the pivotal trials already completed, discuss the current controversies and complexities in the treatment decision-making, and postulate on what likely lies ahead. This paper will highlight the complexities of decision-making optimal treatment recommendations for patients with symptomatic and asymptomatic carotid stenosis.